Factores socioculturales relacionados con el embarazo reincidente en adolescentes atendidas en el Hospital Docente Madre-Niño San Bartolomé, Lima - Chura Muñuico, Ruth (2019)
Objective: To determine the socio-cultural factors that relate to repeat pregnancy in adolescents who attended theMother Child Teaching Hospital San Bartolomé during the month of June 2012, Lima-Peru. Material and Methods:The present research is a descriptive correlational and cross-sectional. The population consisted of 120 pregnantadolescents who were treated in the outpatient and hospitalized pregnant teenagers in service “Teenage Mother”.Instrument was used as a survey data collection, the same that was validated by experts and is managed by theresearchers in the month of June 2012. The information was processed using the Statistical Package for the SocialSciences SPSS version 15 and statistical significance of the results was established with the chi-square test. Results:The study shows that the average age of the adolescents surveyed is 17 years, 51.7% were single, also reveals that67.5% of adolescents drop out of study. To the question “With whom live at home?”, Only 34.2% of adolescents livewith their parents and siblings. On the economic solvency 50.8% receive financial support from their partner. Oncultural factors shows that 45% of teenagers have completed secondary education. On knowledge of contraceptivemethods, 85% said they used contraception to avoid becoming pregnant. Similarly, 58.3% of adolescents were usingcondoms for birth control before becoming pregnant. When asked, “Why did you use?” 50% said it was because ofneglect or oblivion. It also shows that 10.8% of them have had recurrent pregnancy. Conclusions: The relationshipbetween socio-cultural factors and recurrent pregnancy is insignificant. (> .05).